2010
DOI: 10.1016/j.atherosclerosis.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Update of the Portuguese Familial Hypercholesterolaemia Study

Abstract: a b s t r a c tThe main aim of the Portuguese Familial Hypercholesterolaemia Study is to identify the genetic cause of hypercholesterolaemia in individuals with a clinical diagnosis of Familial Hypercholesterolaemia (FH). A total of 1340 blood samples were collected from 482 index patients and 858 relatives with the collaboration of clinicians from several hospitals all over the country. The genetic diagnosis of FH in this study is based on the analyses of three genes: LDLR, APOB and PCSK9. In the last 10 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 23 publications
2
38
0
1
Order By: Relevance
“…The genetic diagnosis of FH was performed by the molecular analysis of APOB (two fragments of exons 26 and 29), LDLR (including the study of splice regions and large rearrangements), and PCSK9 genes as reported previously ( 26 ). Mutations were considered to be pathogenic if cosegregation of the mutation with the phenotype was observed and if mutations were previously described in other populations.…”
Section: Molecular Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic diagnosis of FH was performed by the molecular analysis of APOB (two fragments of exons 26 and 29), LDLR (including the study of splice regions and large rearrangements), and PCSK9 genes as reported previously ( 26 ). Mutations were considered to be pathogenic if cosegregation of the mutation with the phenotype was observed and if mutations were previously described in other populations.…”
Section: Molecular Analysismentioning
confidence: 99%
“…No mutations were found in the PCSK9 gene. In the remaining 148 children (62.4%), no mutations considered pathogenic were identifi ed using the current molecular biology techniques previously published ( 26,27 ).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last ten years, the Portuguese FH Study identified 80 different mutations in the LDLR gene, in 165 unrelated index patients, 34 being exclusive to the Portuguese population [22]. The mutation found in the LDLR gene of our family has not been previously described in the literature, and is to date exclusive to our study population, so we call it Azorean-1 mutation.…”
Section: Discussionmentioning
confidence: 80%
“…28 In addition, a Portuguese ADH study found only 48% of its total received cases with clinical diagnosis of ADH had genetic defects on LDLR, APOB or PCSK9, leaving the other 52% of ADH cases with possible undiscovered gene mutations. 29 In a study by Garcia et al, 30 the researchers used gene chip (robo arrays) to resequence the coding regions of 10 key genes of lipid metabolism in 80 dyslipidemic cases. In all, 14 non-synonymous and 22 synonymous SNPs were identified, which were confirmed by conventional sequencing.…”
Section: Resultsmentioning
confidence: 99%